Phenolic Compounds from Arundina graminifolia and Their Anti-Tobacco Mosaic Virus Activities - Gao, Zerui; Xu, Shitao; Wei, Jie; Shi, Honglin; Li, Zhong; Hu, Qiufen (Asian Journal of Chemistry, 2012)
A new phenolic compounds, gramphenol A, together with three known phenols (2-4), were isolated from the whole plant of Arundina gramnifolia. The structure of compounds 1-4 was elucidated by spectroscopic methods including extensive 1D and 2D NMR techniques. The anti-tobacco mosaic virus (anti-TMV) activities were evaluated for compounds 1-4. The results reveal that compound 1 exhibits modest anti-tobacco mosaic virus activities.